2015
DOI: 10.1890/14-2153.1
|View full text |Cite|
|
Sign up to set email alerts
|

Reconciling the role of organic matter pathways in aquatic food webs by measuring multiple tracers in individuals

Abstract: Few studies measure multiple ecological tracers in individual organisms, thus limiting our ability to differentiate among organic matter source pathways and understand consequences of dietary variation and the use of external subsidies in complex food webs. We combined two tracers, stable isotope (SI) ratios and fatty acids (FA), to investigate linkages among ecological compartments (water column, benthos, riparian zone) in food webs in waterholes of a dryland river network, the Border Rivers in southwestern Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 67 publications
5
29
0
Order By: Relevance
“…[PUFA] consumer /[PUFA] algae ). Data used for subtropical rivers were fromJardine et al (2015) DHA is selectively and highly retained over other PUFA in fish, consistent with all reviewed datasets. It is still not clear if the high retention of DHA in fish is mainly driven by dietary DHA…”
mentioning
confidence: 85%
“…[PUFA] consumer /[PUFA] algae ). Data used for subtropical rivers were fromJardine et al (2015) DHA is selectively and highly retained over other PUFA in fish, consistent with all reviewed datasets. It is still not clear if the high retention of DHA in fish is mainly driven by dietary DHA…”
mentioning
confidence: 85%
“…The stream ecology community has classically considered the allochthonous inputs to be the key basal resource because of their quantitative dominance over in‐stream primary production in low‐order systems and larger, turbid, and heterotrophic rivers (Vannote, Minshall, Cummins, Sedell & Cushing, ). However, more recently there has been a shift in emphasis to the disproportionate importance of autotrophic producers to animal consumer production in streams and larger rivers (Brito, Moulton, De Souza & Bunn, ; Bunn, Davies & Winning, ; Hayden, McWilliam‐Hughes & Cunjak, ; Jardine et al., ; Lau, Leung & Dudgeon, ,b; Lewis, Hamilton, Rodríguez, Saunders & Lasi, ; Neres‐Lima et al., ; Thorp & Bowes, ; Thorp & Delong, ). Conversely, lakes have classically been thought to be driven by autochthonous production (Carpenter, Kitchell & Hodgson, ), but recent studies have suggested that terrestrial carbon inputs support approximately 30%–70% of the zooplankton as well as zoobenthos and fish production (Berggren, Ziegler, St‐Gelais, Beisner & del Giorgio, ; Berggren et al., ; Carpenter et al., ; Cole et al., , ; Grey, Jones & Sleep, ; Jansson, Persson, De Roos, Jones & Tranvik, ; Karlsson, Jonsson, Meili & Jansson, ; Pace et al., , ; Tanentzap et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Allochthonous flow of terrestrial carbon into aquatic food webs (allochthony) is thought to be an underestimated component of the global carbon cycle (Boyero et al, ; Hanson, Pace, Carpenter, Cole, & Stanley, ). Allochthony is commonly studied using naturally occurring carbon and nitrogen isotopes (Brett et al, ; Jardine et al, ; Tanentzap et al, ), yet methodological constraints have thus far hindered the formulation of a clear consensus about the role of terrestrial organic carbon in aquatic ecosystems (Brett et al, ).…”
Section: Introductionmentioning
confidence: 99%